Determinants Of Compliance Of Msme Taxpayers In Bandar Lampung - Risna Shafa Amelia; Dedi Irawan; Afrizal Nilwan (Cita konsultindo, 2024)
This research is motivated by the consistent non-compliance of MSME taxpayers, especially in Bandar Lampung City. The purpose of this study is to observe the impact of tax rates, tax understanding, and tax sanctions on MSME taxpayer compliance and the role of tax incentives in moderating the effect of tax rates, tax understanding, and tax sanctions on MSME taxpayer compliance. This research uses a quantitative approach. The population of this study were MSME players in Bandar Lampung, with purposive sampling used as a sample selection method. The results showed that tax rates, tax understanding, and tax sanctions have a positive and significant impact on MSME taxpayer compliance. Tax incentives can buffer the impact of tax rates on taxpayer compliance, and tax incentives weaken the impact of tax understanding and tax sanctions on MSME taxpayer compliance. The importance of the amount of tax rates, the understanding of MSME actors about taxation, and tax sanctions will encourage MSME actors to be more compliant in their tax payments.